First Vertical Land Movement Estimates on South Georgia Island: An Impact Study on Sea Level Change from Tide Gauge and Altimetry Measurements - TEFERLE, Felix Norman; HUNEGNAW, Addisu; ABRAHA, Kibrom Ebuy; Woodworth, Phil; Williams, Simon; Hibbert, Angela; Smalley, Robert; Dalziel, Ian; Lawver, Larry (2017)
South Georgia Island in the Southern Atlantic Ocean has been a key location for the seismic, geomagnetic and oceanic global monitoring networks. However, no permanent geodetic monitoring station had been established there despite the lack of observations from this region within, for example, the International GNSS Service (IGS) network of Global Navigation Satellite System (GNSS) stations. Then, in 2013 the King Edward Point (KEP) Geodetic Observatory was established with a focus on sea level studies and in support of general geoscience applications. Currently, this observatory located roughly half-way along the main island and along its northern coastline, consists of two GNSS stations (KEPA and KRSA) with local benchmark networks, allowing the height determinations from the GNSS antennas to be transferred to the KEP tide gauge (GLOSS ID 187) and forming a height reference within the International Terrestrial Reference Frame. In late 2014, three additional GNSS stations (SG01, SG02 and SG03) were established, all on small islands at the perimeter of the main island. Together the stations provide the best possible opportunity to study various geophysical processes in the region. With the GNSS-derived position time series partly reaching over 4.5 years in length, it has become possible to provide first estimates of vertical land movements for the island and KEP with its surrounding area. Together with four precise levelling campaigns of the benchmark network in 2013, 2014 and two in 2017, it has also been possible to investigate the very local character of the vertical motions, ie. the stability of the jetty upon which the tide gauge is mounted. Our measurements show that while South Georgia Island and the area around KEP are rising, the jetty and tide gauge are subsiding. In this study, we will present the preliminary results from the GNSS and levelling measurements and will discuss their impact on the sea level record from the KEP tide gauge which is ideally situated in a mid-ocean location for satellite ...